2012
DOI: 10.1038/sc.2012.75
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the development of pressure ulcers after spinal cord injury

Abstract: SCI patients are a heterogeneous group and the risk factors associated with PU may vary in specific subgroups. Different models are needed to describe PU in SCI patients depending on the patient's age and the time passed since SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 18 publications
3
35
0
11
Order By: Relevance
“…Ten articles were identified that reported the prevalence or incidence of PUs in community dwellers from 6 months to 20 years after injury. [24][25][26][27][28][29][30][31][32][33] Of note, very few of these study subjects were reported to have undergone SCI rehabilitation. These 10 papers reported a PU prevalence of 26.7-46.2%, mean of 35.2%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten articles were identified that reported the prevalence or incidence of PUs in community dwellers from 6 months to 20 years after injury. [24][25][26][27][28][29][30][31][32][33] Of note, very few of these study subjects were reported to have undergone SCI rehabilitation. These 10 papers reported a PU prevalence of 26.7-46.2%, mean of 35.2%.…”
Section: Resultsmentioning
confidence: 99%
“…2,42 Because these healthcare providers lack SCI training, they struggle to manage PU risk factors in their patients and often fail to educate their patients about ongoing PU prevention strategies. In their letter to the editor responding to the 2012 study of PU risks in Iran by Eslami et al, 31 Rathore and Mansoor 43 note that 'lack of knowledge regarding PU prevention on the part of the doctors' is one of the 'four major reasons for PU occurrence' in Pakistan. Indeed, without access to specialty guidance, even the most educated and motivated person with SCI is prone to complications.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported age to be a risk factor for PU development. 21 Although previous studies have reported association between sex and development of PUs in individuals with SCI, 22 this study found no such association in both acute care hospitalization and inpatient rehabilitation. Individuals with AIS A were at increased risk to develop PUs than AIS C and AIS D, similar to previous studies.…”
Section: Discussionmentioning
confidence: 82%
“…[1][2][3] The incidence of TSCI ranges from 3.6 to 195.4 patients per million around the world 4 and 25.5 per million per year in developing countries. 5 A prerequisite to the development of effective therapies for TSCI is a detailed understanding of the pathophysiological events occurring after injury.…”
Section: Introductionmentioning
confidence: 99%